Paradise of the damned : the true story of an obsessive quest for El Dorado, the legendary city of gold - Thomson, Keith, 1965- (Little, Brown and Company, 2024)
"As early as 1530, reports of El Dorado, a city of gold in the South American interior, beckoned to European explorers. Whether there was any truth to the stories remained to be seen, but the allure of unimaginable riches was enough to ensnare dozens of would-be heroes and glory hounds in the desperate hunt. Among them was Sir Walter Raleigh: ambitious courtier, confidant to Queen Elizabeth, and, before long, El Dorado fanatic. Entering the Elizabethan court as an upstart from a family whose days of nobility were far behind them, Raleigh used his military acumen, good looks, and sheer audacity to scramble into the limelight. Yet that same swagger proved to be his undoing, as his secret marriage to a lady-in-waiting enraged Queen Elizabeth and landed him in the Tower of London. Between his ensuing grim prospects at court and his underlying lust for adventure, the legend of El Dorado became an unwavering siren song that hypnotized Raleigh. On securing his release, he journeyed across an ocean to find the fabled city, gambling his painstakingly acquired wealth, hard-won domestic bliss, and his very life. What awaited him in the so-called New World were endless miles of hot, dense jungle packed with deadly flora and fauna, warring Spanish conquistadors and Indigenous civilizations, and other unforeseen dangers. Meanwhile, back at home, his multitude of rivals plotted his demise. Paradise of the Damned, like Keith Thomson's critically acclaimed Born to Be Hanged, brings this story to life in lush and captivating detail. The book charts Raleigh's obsessive search for El Dorado--as well as the many doomed expeditions that preceded and accompanied his--providing not only an invaluable history but also a gripping narrative of traveling to the ends of the earth only to realize, too late, that what lies at home is the greatest treasure of all"--